2022
DOI: 10.1177/07067437221097903
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Light Therapy for Seasonal and Non-Seasonal Depression: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objectives To determine the efficacy and safety of blue-light therapy in seasonal and non-seasonal major depressive disorder (MDD), by comparison to active and inactive control conditions. Methods We searched Web of Science, EMBASE, Medline, PsycInfo, and Clinicaltrials.gov through January 17, 2022, for randomized controlled trials (RCTs) using search terms for blue/blue-enhanced, light therapy, and depression/seasonal affective disorder. Two independent reviewers extracted data. The primary outcome was the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Light, as a fundamental dimension of the physical environment, acts as a vital contributor affecting human behavior and health [ 1 , 2 , 3 ]. In addition to light’s effects on image forming (IF) function, a growing number of studies have been conducted to explore the non-image forming (NIF) effects of light during recent decades [ 4 , 5 ], among which the effects of light on alertness [ 6 ], affective state [ 7 ], cognitive performance [ 8 ], sleep and circadian rhythms [ 9 ] were widely reported. In addition to the effects of ambient light on psychological and biological functioning, the associations between ambient light and social behavior attributes have also been investigated in a few field and laboratory studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Light, as a fundamental dimension of the physical environment, acts as a vital contributor affecting human behavior and health [ 1 , 2 , 3 ]. In addition to light’s effects on image forming (IF) function, a growing number of studies have been conducted to explore the non-image forming (NIF) effects of light during recent decades [ 4 , 5 ], among which the effects of light on alertness [ 6 ], affective state [ 7 ], cognitive performance [ 8 ], sleep and circadian rhythms [ 9 ] were widely reported. In addition to the effects of ambient light on psychological and biological functioning, the associations between ambient light and social behavior attributes have also been investigated in a few field and laboratory studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Experimental design. In this study, both RCTs and non-randomized experimental studies were included for therapeutic efficacy evaluation, while few previous studies have discussed the aspect by merely including RCT studies ( 3 ) since total blindness for RCTs is quite hard to achieve, as mentioned. Since intuitive, neurophysiological, and chronobiological light therapies are distinct from pharmaceutical interventions, we deduced less differentiation caused by design methodology and combined overall outcomes by fully discussing between-group differences and comparing dose-response saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dysfunction of the circadian system has been strongly linked to psychological disorders, light therapy has been particularly successful in treating such conditions ( 2 ). However, skeptics contend that light therapy's efficacy may be little better than a placebo under great varieties of light administration protocols (e.g., white light or monochromatic light, various intensities) ( 3 ), as well as malady conditions. The skepticism surrounding the efficacy of light therapy for treating a wide range of maladies is rooted in the uncertainty of light dosing ( 2 ), whether in monotherapy studies or combination cases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the spectral composition of light changes over the seasons, with more blue light in the summer compared to the winter [ 149 ]. Secondly, despite contradictory results about the efficacy of blue-light therapy in the treatment of seasonal and non-seasonal major depressive disorders, some studies reported that blue-light therapy, including using LEDs, is an effective treatment for SAD, but importantly requires lower irradiance and/or shorter exposure duration than standard white-light therapy [ 140 , 150 , 151 , 152 ], which may favour treatment compliance. Thirdly, certain individuals with genetic mutations within the melanopsin gene have an increased risk of SAD [ 153 ].…”
Section: Emotional Processing and Moodmentioning
confidence: 99%